1983
DOI: 10.1097/00004032-198301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Retention of 14C-DTPA in Human Volunteers After Inhalation Or Intravenous Injection

Abstract: This study in human volunteers was designed to compare the retention of diethylenetriaminepentaacetic acid (DTPA) in the body after intravenous (i.v.) injection with that following inhalation by using a 14C labelled tracer. After i.v. injection retention in the blood could be described by three exponential components with half-times of about 1.4 min (approximately 60%) 14.3 min (approximately 20%) and 95 min (approximately 20%). By 24 hr more than 99% of the 14C-DTPA had been excreted in the urine and less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…It is nearly completely excreted 12 hours after its administration (Gusev et al, 2001;REAC/TS, 2002). A study on two healthy volunteers evidenced that in 24 hours, 99% of the Ca-DTPA injected was excreted in the urines and that less than 0.5% remained in the plasma (Stather et al, 1983).…”
Section: Exposure To Actinides: Report On Ca-dtpa Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is nearly completely excreted 12 hours after its administration (Gusev et al, 2001;REAC/TS, 2002). A study on two healthy volunteers evidenced that in 24 hours, 99% of the Ca-DTPA injected was excreted in the urines and that less than 0.5% remained in the plasma (Stather et al, 1983).…”
Section: Exposure To Actinides: Report On Ca-dtpa Injectionsmentioning
confidence: 99%
“…From human data (Stather et al, 1983), the modelling results in plasma transfer rates to extra cellular fluids (ECF) (K1) extracellular fluids and from ECF to plasma (K2). These are very short with respective biological periods of 2.5 and 6.3 minutes.…”
Section: Ca-dtpa Pharmacokinetic Modelmentioning
confidence: 99%
“…DTPA is hydrophilic and is unlikely to penetrate cells to any great extent 39 . Early pharmacokinetic studies in animals 40,41 and in humans 42 showed that DTPA is very poorly distributed into tissues and is rapidly eliminated from the body via urine excretion after either intravenous injection or inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of its ability to chelate Pu in body fluids, DTPA is hydrophilic and thus does not penetrate cells to any great extent (4). Besides, early pharmacokinetic studies in animals (5,6) and in humans (7) showed that DTPA is generally very poorly distributed to tissues and is rapidly eliminated from the body after inhalation or intravenous injection.…”
Section: Introductionmentioning
confidence: 99%